2017
DOI: 10.14419/ijac.v5i1.7155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activities of some (E)-N'-1-(substituted benzylidene)benzohydrazides

Abstract: About ten substituted (E)-N-1-(substituted benzylidene) benzohydrazides have been synthesized. They are analyzed by their analytical, ultra violet (UV), Fourier transform-IR (FT-IR) and nuclear magnetic resonance (NMR) spectral data and evaluated by antimicrobial activities such antibacterial and antifungal activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 11 publications
(12 reference statements)
1
17
0
Order By: Relevance
“…A significant part among thousands of new biologically active compounds synthesized each year by medicinal chemists around the world belongs to the group of hydrazide‐hydrazones (Bala, Uppal, Kajal, Kamboj, & Sharma, ; Popiołek, ; Rollas & Küçükgüzel, ). This is due to the fact that this group of compounds possesses very interesting and broad spectrum of biological properties (Bala et al, ; Popiołek, ; Rollas & Küçükgüzel, ), which include antimicrobial (Backes, Neumann, & Jursic, ; Manikandan et al, ; Metwally, Abdel‐Aziz, Lashine, Husseiny, & Badawy, ; Rollas, Gulerman, & Erdeniz, ; Zha et al, ), anticancer (Kumar, Kumar, Ghosh, & Shah, ; Nasr et al, ; Nasr, Bondock, & Youns, ; Nikolova‐Mladenova, Momekov, Ivanov, & Bakalova, ; Sreenivasulu, Reddy, Sujitha, Kumar, & Raju, ; Tantak et al, ), anti‐inflammatory (Gökçe, Utku, & Küpeli, ; Moldovan et al, ; Sondhi, Dinodia, & Kumar, ), anticonvulsant (Dehestani et al, ) and analgesic activity (Navidpour, Shafaroodi, Saeedi‐Motahar, & Shafiee, ).…”
Section: Introductionmentioning
confidence: 99%
“…A significant part among thousands of new biologically active compounds synthesized each year by medicinal chemists around the world belongs to the group of hydrazide‐hydrazones (Bala, Uppal, Kajal, Kamboj, & Sharma, ; Popiołek, ; Rollas & Küçükgüzel, ). This is due to the fact that this group of compounds possesses very interesting and broad spectrum of biological properties (Bala et al, ; Popiołek, ; Rollas & Küçükgüzel, ), which include antimicrobial (Backes, Neumann, & Jursic, ; Manikandan et al, ; Metwally, Abdel‐Aziz, Lashine, Husseiny, & Badawy, ; Rollas, Gulerman, & Erdeniz, ; Zha et al, ), anticancer (Kumar, Kumar, Ghosh, & Shah, ; Nasr et al, ; Nasr, Bondock, & Youns, ; Nikolova‐Mladenova, Momekov, Ivanov, & Bakalova, ; Sreenivasulu, Reddy, Sujitha, Kumar, & Raju, ; Tantak et al, ), anti‐inflammatory (Gökçe, Utku, & Küpeli, ; Moldovan et al, ; Sondhi, Dinodia, & Kumar, ), anticonvulsant (Dehestani et al, ) and analgesic activity (Navidpour, Shafaroodi, Saeedi‐Motahar, & Shafiee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Their activity against tested fungi was higher or equal to the activity of Amphotericin B (Table 14) [15]. Analysis of the diameter of zone of inhibition growth (mm) of compounds obtained by Manikandan et al revealed that only hydrazide-hydrazone 42 had shown good antifungal sensitivity against three species of fungi (Figure 33, Table 15) [16]. Nitrofurazone analogues synthesized by Popiołek and Biernasiuk also showed interesting antifungal activity.…”
Section: Antifungal Activitymentioning
confidence: 97%
“…Hydrazidehydrazones 5 and 6 showed no cytotoxic activity at 0-500 µg/mL concentrations [15]. Analysis of the values of the zone of inhibition growth of compounds synthesized by Manikandan et al revealed that among obtained hydrazide-hydrazones, only derivative with 4-fluorophenyl substituent 7 had shown satisfactory antibacterial sensitivity in comparison with ciprofloxacin (Figure 5, Table 3) [16]. The results of the study by Popiołek and Biernasiuk indicated that synthesized and in vitro examined hydrazide-hydrazones exhibited a wide spectrum of antibacterial activity against tested reference bacteria.…”
Section: Antimicrobial Activity 21 Antibacterial Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…Since the carbonyl group readily reacts with N-nucleophiles, we have taken this route of addition of aroylhydrazones. The latter were chosen primarily as additional pharmacophores, since aroylhydrazones are widely used in medicine as broad-spectrum bactericides [13][14][15] and anti-tuberculosis drugs [16][17][18]. Other examples of medical applications of these compounds are as anti-inflammatory [19] and antidepressant agents [20].…”
Section: Chemistrymentioning
confidence: 99%